(untitled) - Kajima, Morinosuke (Tokyo, 1976)
This book consists of the following many parts: conclusion of the first Anglo-Japanese agreement of Alliance, The far East before the Russo-Japanese war and Russo-Japanese negotiations on manchuria and Korea, Opening of the Russo-Japanese war and its consequences in Korea and China, good offices of United States president roosevelt, the portsmouth peace conference, the portsmouth peace conference, conlusion of the second and third Anglo-Japanese agreement of Alliance.